Ambiguity in the Construction of Verb-based Nominalization in Bahasa Indonesia - Dwi Wulandari; FX Sawardi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2026)
This article examines the nominalization of verbs in Bahasa Indonesia, reviews the affixes used to nominalize verbs, and considers the potential for ambiguity in their structure and meaning. This qualitative study used data from news reports on kompas.com and sindonews.com. The results show that some deverbal nouns have ambiguous structures, indicating that the same noun may be derived from both transitive and intransitive verbs, and that the same noun may also be derived from transitive verbs with different derivations. Some noun phrases may show an ambiguous relation between agent and patient. Sometimes it is difficult to decide whether the noun attached to the deverbal noun functions as an agent or a patient because of the tendency to omit the preposition between them. There are three reasons justifying why the preposition in such a construction may be omitted; the function of the prepositional phrase as an adjunct, the semantic roles of the noun and deverbal noun, and the practicality of usage